ANALISIS INFORMASI LAPORAN KINERJA KEUANGAN DALAM KEPUTUSAN INVESTASI/BISNIS PADA PT BPR SARIMADU (PERSERODA) - Nurman, Toni; Marantika, Absor; Zulher, Zulher (Jurnal Ekonomi Bisnis Kompetif, 2025)
The research was conducted at PT BPR Sarimadu (Perseroda). reviewed from the liquidity and solvency aspects using descriptive research methods and data collection techniques through documentation and interviews with the Board of Directors in the form of secondary data, namely the annual report of PT BPR Sarimadu (Perseroda), there was an increase in the liquidity ratio as measured by the current ratio in 2022 and compared to the internal average of PT BPR Sarimadu (Perseroda). which shows that the company is less able to pay off short-term obligations when they fall due. Although there has been an increase, the increase in the current ratio has not been significant so that it has not been able to change the ratio level to the standard point stated in the theory of this research, namely 200%. This results in the company being less secure in paying short-term obligations when they fall due or the creditor's position is still not secure in other words the company is illiquid. This means that the company's management has not been able to strictly supervise working capital items as evidenced by the large amount of short-term debt. PT BPR Sarimadu (Perseroda) is seen from the level of liquidity of the company as illiquid but seen from the solvency side of the company as solvable. PT BPR Sarimadu (Perseroda) is less able to maintain its liquidity level. However, it does not mean that investment in the company is not attractive, because the company can still maintain the stability of its solvency, in fact it is very good when compared to the theory in this study